2015
DOI: 10.12816/0024440
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Sukuk as a Tool of Monetary Policy

Abstract: In interest based Capitalist system, monetary policy (MP) has become mostly ineffective in increasing output, and employment in recent years. Recession in the form of low or even negative growth rates of real GDP and high unemployment rates have set in and there are no signs of robust recovery in many of the capitalist economies. Today, conventional expansionary monetary policy appears to be creating more adverse effects than increasing real output and cutting unemployment rates. This paper attempts to explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 6 publications
0
16
0
1
Order By: Relevance
“…Selim (2013) argues that MP based on mu Á d arabah is more effective than IBMP. Selim (2015) further demonstrates that MP based on Á sukūk works better when Á sukūk are bought and sold in the open market by the CB. Islamic MP involving buying and selling of securities was initially emphasised by Chapra (1982) and Siddiqi (1982).…”
Section: Literature Reviewmentioning
confidence: 82%
“…Selim (2013) argues that MP based on mu Á d arabah is more effective than IBMP. Selim (2015) further demonstrates that MP based on Á sukūk works better when Á sukūk are bought and sold in the open market by the CB. Islamic MP involving buying and selling of securities was initially emphasised by Chapra (1982) and Siddiqi (1982).…”
Section: Literature Reviewmentioning
confidence: 82%
“…Selim (2015) has also demonstrated that Sukuk can be used as effective tools of MP. Furthermore, Selim (2015) showed that MP based on buying and selling Sukuk in open market operations is relatively more effective than conventional interest based MP. Therefore, QH-based MP can be applied along with other Sharia-compliant modes of financing including profit-based models.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Interest based monetary policy which had been pursued in most of the countries of the world, including in the muslim majority countries had created the problems of under investment spending, unemployment, depressed economic growth rates, perpetual poverty, and periodic financial crisis. In current times, we have plenty of Islamic economic theories, and these theories and principles can easily be implemented for pursuing successful Islamic monetary policy (Selim 2015(Selim , 2019(Selim , 2020, especially for providing access to the lender of last resort services for the Islamic Banks (Selim & Hassan, 2020); for easily financing homes with Ijarah based diminishing Musharaka (Selim 2020a); for eliminating interest in trade or Riba al Fadl in foreign currency transactions (Selim 2021); for pursuing Sukuk based open market operation as part of Islamic Monetary policy (Selim 2015) instead of Treasury Bills and other interest based financial papers and securities; for pursuing interest free financing of infrastructure projects and redesigning it with Qard Hasan so that it will be acceptable to all Islamic Schools of Fiqh (Selim 2020); for providing Islamic business based Takaful insurance where the policy holders are both owners and risk takers and there are no middlemen who often deprive the share and benefits of the policy holders; here Policy holders are active participants and driving forces of such Islamic Business based Takaful Insurance and receive hundreds of thousands of Dinars (Here Dinar refers to Bahraini Dinar where 1 Bahraini Dinar=US$2.65) during their old age when they need it the most, (Selim 2015a); for providing Islamic value based Islamic Cooperative model for poverty elimination (Selim & Farooq, 2020); for permanently eliminating interest costs in trade deficits financing (Selim 2013) but in reality these wonderful Islamic economic theories have not been implemented correctly. This paper is a humble effort to urge nations of the world, especially the members of the Organization of Islamic Cooperation (OIC) countries to truly implement these theories and thus solving all the above problems of poverty, huge interest payments as part of trade deficit financing, unemployment, low income, widespread interest including Riba al Fadl or interest originating in trade, ineffectiveness in monetary policy and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The motivation of this study is to highlight the importance of all the above theories and many other Islamic economic theories and to create an urgency to adopt such Islamic economic theories for achieving full employment, potential real GDP, eliminating poverty, Riba or interest and many other economic and social problems. Despite the development of full fledged and effective Islamic monetary policy as mentioned above (Selim 2015(Selim , 2019(Selim , 2020, the members of the OIC countries have so far paid little importance but many members of the Organization for Economic Cooperation and Development (OECD) countries are now currently pursuing interest free monetary policy in the form of zero central bank interest rate or even negative central bank interest rate. Such interest free monetary policy yields relatively better economic performance and thus more effective in controlling inflation rates and lowering unemployment rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation